К проблеме определения экологического дискурса - Руденко, Н.С. (Культура народов Причерноморья, 2014)
В статье рассматриваются основные подходы к экологическому дискурсу, применяемые в
отечественных филологических исследованиях. Показано, что выделяемый по тематическому
критерию экологический дискурс представляет собой совокупность текстов, макротемой которых
являются экологические отношения, реализующиеся на уровнях «организм – среда обитания»,
«общество – окружающая среда» или «человек – природа», и является дискурсом институциональным.
Его социально-ситуативную специфику составляют такие свойства, как динамичность и
неоднородность, обусловленные экстралингвальными факторами. Стаття розглядає основні підходи до екологічного дискурсу, що їх застосовано у вітчизняних
філологічних дослідженнях. Показано, що екологічний дискурс виокремлюється за тематичним
критерієм. Він складається з сукупності текстів, об’єднаних макротемою екологічні взаємин, які
реалізуються на рівнях «організм – середовище», «суспільство – довкілля», «людина – природа».
Екологічний дискурс є інституціональним. Його соціокультурну специфіку складають таки ознаки, як
динамічність і неоднорідність, зумовлені екстралінгвальнимі факторами. The article deals with the notion of environmental discourse used by Russian and Ukrainian scholars.
The author considers the general definition of discourse and the criteria of its identification and classification.
Reviewing the approaches to environmental discourse definition, the author gives particular attention to the
controversial issues of environmental discourse structure and to the problem of considering literary texts as a
marginal part of environmental discourse. It has been shown that environmental discourse is singled out into a
separate discourse type in accordance with the thematic criterion. It can be defined as the collection of texts
united by the macro-theme of environmental relations which can manifest themselves as the interaction between
an organism and its habitat, the society and the environment, or man and nature. According to the addresseraddressee
criterion environmental discourse is institutional. From the socio-situational point of view it is
heterogeneous and includes such types as scientific and media discourse. Arising at the cross-sections of
significant human activities such as politics, economics, science, education, environmental discourse is both
heterogeneous and dynamic and incorporates different text types.